INTERFERENCE OF JAVANESE BOJONEGORO DIALECT IN INDONESIAN LANGUAGE LEARNING HIGH CLASS STUDENTS SDN 1 JIPO, KEPOHBARU, BOJONEGORO - Etty Umamy; Kisyani Laksono; Mintowati Mintowati; Didik Nurhadi (Universitas Islam Lamongan, 2022)
Interference is one of the effects of language contact. Interference is interpreted as interference, interference, or the inclusion of language elements into other languages. This research is intended to find out the forms of interference and possible solutions to improve Indonesian language learning, especially for students at SDN 1 Jipo, Kepohbaru, Bojonegoro. This research is a type of descriptive qualitative research. The data in this study are transcripts of student conversations when learning Indonesian takes place. Data collection was carried out using observation, recording, interviewing, and listening techniques. Then do preduction and presentation of data, as well as drawing conclusions. The last step, the researchers conducted time triangulation, to experts, and discussions. Based on the results of data analysis,five forms of language interference were found, namely cultural interference, semantics, syntax, morphology and phonology. Cultural interference occurs due to students' lack of knowledge of the target language culture (B2). Semantic interference occurs in the use of words that have variables in a language. Syntactic interference, including the grammatical system of B1 mixed with B2. Morphological interference, occurs in the formation and change of word formsin the use of B1 due to friction with B2. Phonological interference, there are errors in pronunciation or pronunciation of sounds in Indonesian because they are influenced byregional language (Javanese).Language interference is difficult to eliminate so we need a way to minimize its impact. The methods that can be used are the teacher's efforts, student awareness, and the role of the environment.